Potensi Ekstrak Kasar Ulva lactuta dalam Meningkatkan Total Haemocyte Count (THC) dan Aktivitas Fagositosis pada Udang Vaname (Litopenaeus vannamei) - Suleman Suleman; Sri Andayani; Ating Yuniarti (Faculty of Science and Technology University Ibrahimy, 2019)
Acauses of the decrease in vaname shrimp production was vibriosis. Vibriosis is caused by vibrio bacteria. A vibrio bacteria that plays a role in vibriosis is vibrio harveyi. Managing of diseases caused by vibrio harveyi is one of the best that provides immunostimulant assistance from natural ingredients derived from seaweed. Ulva lactuta is a green seaweed that has different substances that contain immune. Some of the compositions contained in Ulva Lactutawere Flavonoid Compositions, and the Composition of Polysaccharides that are Combined with Immunimulants The purpose of this study was to determine the effect and dosage used to improve the immune system in vaname shrimp. Combined with THC and Fagocytosis in the hemolim on vaname shrimp before infection and after infection with Vibrio harveyi bacteria.A dose of 2 ppm showed a significant difference (p <0.05) for all treatments.